2013
DOI: 10.7567/jjap.52.030201
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of Grains of Silica Colloidal Crystals by Centrifugation in an Inverted-Triangle Internal-Shaped Container

Abstract: We successfully fabricated large grains of silica colloidal crystals in an inverted-triangle internal-shaped container (inverted-triangle container) by centrifugation. The largest grain in the container was much larger than that in a container which has a flat bottom and constant width (flat-bottomed container). The edged bottom of the inverted-triangle container eliminated the number of the grains, and then the broadened shape of the container effectively widened the grains.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…During sedimentation by centrifugal force, the hydrodynamic effects [17][18][19][20] may not be neglected. However, since the centrifugal force in the experiment 13) is much weaker than that in other experiments, [21][22][23][24][25] the hydrodynamic effects may be smaller than those in other experiments. Thus, in order to simplify the model, we neglect the hydrodynamic effects and carry out simulation.…”
Section: Modelmentioning
confidence: 67%
See 3 more Smart Citations
“…During sedimentation by centrifugal force, the hydrodynamic effects [17][18][19][20] may not be neglected. However, since the centrifugal force in the experiment 13) is much weaker than that in other experiments, [21][22][23][24][25] the hydrodynamic effects may be smaller than those in other experiments. Thus, in order to simplify the model, we neglect the hydrodynamic effects and carry out simulation.…”
Section: Modelmentioning
confidence: 67%
“…Large domains of ordered particles are formed in bulk, which agrees with experiment. 13) In our simulation, two walls cross orthogonally at an edge. If a {1, 1, 1} face of the fcc structure or a {0, 0, 0, 1} face of the hcp structure are formed on the two walls at a time, the expected faces of crystals formed in two walls cannot cross orthogonally.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the methods used to create closepacked colloidal crystals is the centrifugal method. Recently, Hashimoto et al [12] succeeded in creating a large colloidal crystal in a container with an inverted triangular bottom using the centrifugal method. They suggested that the formation of the large grains is caused by suppression of nucleation.…”
Section: Introductionmentioning
confidence: 99%